PERFORMANCE DIAGNOSIS OF SEPTAGE TREATMENT PLANT - Reni Nuraeni; Fitrijani Anggraini (Widyariset, 2015)
The sanitation development target that everybody has access to sanitation infrastructure has not fulfilled yet, and only 65% of 146 units of septage treatment plant operated well. These conditions need to be improved and the first thing to do is analysing existing condition and composing scientific information as a reference for implementation. The aim of this research is to map the condition and management status of septage treatment plant system in 8 cities selected. This research was conducted by assessing the content of septage treatment technologies using technology atlas approach, which consists of elements technoware, humanware, infoware and orgaware. Mapping carried out on two types of septage treatment plant, that uses Imhoff tank and Anaerobic Baffle Reactor (ABR). Mapping was also conducted on the status of rehabilitation and operational conditions for each septage treatment plant.The results of this study concluded that the sophistication level of septage treatment technology is a medium category with coefficient contribution is 50%. Operational conditions of septage treatment plant is almost optimum with the  ability of septage processing is 54%.  A recommendation to increase the performance of septage treatment plant are : improving septage supply, improving the maintenance quality of processing units, improving SOP quality, sharpening tasks and responsibilities as well as improving human resource competencies.